Prevalence of Alcohol Consumption and Knowledge on its Consequences among Young Adult in Ward Number Five at Kachan Kawal Municipality, Nepal - Basnet, Saraswati; Rajbonshi, Sharmila (Bouddhik Abhiyan (बौद्धिक अभियान), 2023)
The harmful use of alcohol causes many disease, social and economic burden in societies. The harmful use of alcohol ranks among the top risk factors for disease, disability and death through world. youth, who start drinking before age 15 years are six time more likely to develop alcohol dependence or abuse later in life than those who begin drinking at or after age 20 years. Aim of the study is to find out the prevalence of alcohol consumption and knowledge on its consequences among young adult (19-39 years) young adult in ward number 5 at Kachan Kawal Municipality, Jhapa. Descriptive cross sectional research design was used in this study. Non probability purposive sampling technique was used to select 50 young adult and semi -structured interview schedule was used to collect data. Data analysis was done on SPSS version 20.0. Descriptive statistics i.e. frequency, mean and standard deviation and inferential statistics i.e. chi square test was used to find the association between dependent and independent variable The finding of the present study revealed that out of 50 respondent 70% had current drinker, with male 44% outnumbering female 24%. Among those consumed alcohol 83.33% have used it before the age of 20 years. More than half of the respondents had been good knowledge on consequences of alcohol consumption i .e 56.0% and 44.0% had poor knowledge. It was concluded that alcohol consumption was high among male than female. There is association between level on knowledge on consequences and alcohol consumption and socio demographical variables.